Electro-organic Nuclear Oxidation: Methoxylation of Aromatic Compounds at Platinum Electrode - Sanjeev Kumar (E-Journal of Chemistry)
The anodic oxidation of aromatic compounds was carried out at controlled potential in the non aqueous methanol-KOH system for the purpose of investigating this type of anodic reaction as a new possible synthetic method. The electroorganic nuclear oxidation was carried out at controlled potential electrolysis in a conventional three electrode cell assembly with platinum plate working as well as counter electrode and saturated calomel electrode as reference electrode. Controlled potential electrolysis was carried out in the solvent methanol and the supporting electrolyte in caustic potash. All the spectral and analytical data were found in good agreement with the synthesized compounds.